Motif Ibu Single Parent Dalam Mendidik Kemandirian Anak di Desa Mejoyolosari Kecamatan Gudo Kabupaten Jombang - Agustin, Fitria Dewi; Listyani, Refti Handini (Paradigma, 2024)
This research aims to determine the motives of single parent mothers in educating children’s independence in Mejoyolosari Village, Gudo District, Jombang Regency. Using a qualitative approach, this research explores social problems with a qualitative descriptive approach. The qualitative research method was chosen because it focuses on in-depth understanding of naturally occurring phenomena, while a qualitative descriptive approach is used to describe problems in detail. The results of this research show that single parents who work full time tend to educate their children strictly. This stems from the condition of the mother who was tired after work. However, on the other hand, the level of independence of children of single parents who work full time tends to be more independent, not dependent on other people and more ready to move on to life in the future. If related to Alfred Schutz’s theory, there are factors that influence the motive for this reason, namely because of the increasing erosion of children’s morals nowadays which is caused by the low level of independence and also the desire of parents not to burden other people. There are two goals expected by single parents in educating children’s independence, namely (1) Being able to complete tasks and obligations without involving other people, (2) Producing a generation that is tough and ready to face life in the future.